Impact of the COVID-19 Pandemic on Physical and Mental Health in Lower and Upper Middle-Income Asian Countries: A Comparison Between the Philippines and China - Tee, Michael; Wang, Cuiyan; Tee, Cherica; Pan, Riyu; Reyes, Patrick W.; Wan, Xiaoyang; Anlacan, Joseph; Tan, Yilin; Xu, Linkang; Harijanto, Chloe; Kuruchittham, Vipat; Ho, Cyrus; et al. (Frontiers in Psychiatry, 2021)
Objective The differences between the physical and mental health of people living in a lower-middle-income country (LMIC) and upper-middle-income country (UMIC) during the COVID-19 pandemic was unknown. This study aimed to compare the levels of psychological impact and mental health between people from the Philippines (LMIC) and China (UMIC) and correlate mental health parameters with variables relating to physical symptoms and knowledge about COVID-19. Methods The survey collected information on demographic data, physical symptoms, contact history and knowledge about COVID-19. The psychological impact was assessed using the Impact of Event Scale-Revised (IES-R), and mental health status was assessed by the Depression, Anxiety and Stress Scale (DASS-21). Findings The study population included 849 participants from 71 cities in the Philippines and 861 participants from 159 cities in China. Filipino (LMIC) respondents reported significantly higher levels of depression, anxiety and stress than Chinese (UMIC) during the COVID-19 (p<0.01) while only Chinese respondents’ IES-R scores were above the cut-off for PTSD symptoms. Filipino respondents were more likely to report physical symptoms resembling COVID-19 infection (p<0.05), recent use of but with lower confidence on medical services (p<0.01), recent direct and indirect contact with COVID (p<0.01), concerns about family members contracting COVID-19 (p<0.001), dissatisfaction with health information (p<0.001). In contrast, Chinese respondents requested more health information about COVID-19. For the Philippines, student status, low confidence in doctors, dissatisfaction with health information, long daily duration spent on health information, worries about family members contracting COVID-19, ostracization, and unnecessary worries about COVID-19 were associated with adverse mental health. Physical symptoms and poor self-rated health were associated with adverse mental health in both countries (p<0.05). Conclusion The findings of this study suggest the need for widely available COVID-19 testing in MIC to alleviate the adverse mental health in people who present with symptoms. A health education and literacy campaign is required in the Philippines to enhance the satisfaction of health information.